Study on splitting of water for production of hydrogen gas using solar energy. - Singh, Vaishali; Chatterjee, Tanushree (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">Hydrogen is a coveted gas: industry uses it for everything from removing sulfur from crude oil to manufacturing vitamins. Since its combustion does not emit carbon dioxide into the atmosphere, there is some belief that it could even fuel a potential "hydrogen economy"-an energy-delivery system based entirely on this one gas. In space, it is the fuel which drives the energy output of stars. But since there is no abundant supply of hydrogen gas that can be simply tapped into, this lighter-than-air gas has to be mass-produced. The choice of water as a raw material to produce hydrogen using sun light gives the impression of an ideal novel approach to supply clean energy. The design of efficient systems for splitting water into hydrogen and oxygen, driven by sunlight is among the most important challenges facing science today, underpinning the long term potential of hydrogen as a clean, sustainable fuel.